EFFECTS OF WORK ENVIRONMENT AND LEADERSHIP STYLE ON WORK STRESS: A STUDY ON PT XXX, KARAWANG, WEST JAVA - Wanta; Tuhagana, Aji; Komala Putri, Ratna (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to obtain empirical evidence and find clarity of phenomena and conclusions about the influence of the work environment and leadership style on work stress in the Quality Control division at PT. XXX. The research design uses descriptive and inductive methods, namely, collect, present, analyze and test hypotheses, and make conclusions and suggestions. The results of the analysis of the research data are: 1) the correlation test of the work environment with the leadership style of 0.382 with a significance value of 0,000, meaning that the figure shows that there is a positive and significant linear relationship between the work environment and the leadership style; 2) The results of the simultaneous determination coefficient test between work environment and leadership style on work stress obtained a value of 33.8%. This means that simultaneously the work environment and leadership style affect work stress by 33.8%, while the remaining 66.2% is influenced by other factors not examined; 3) The direct effect of work environment variables on work stress variables of 0.2642 or 26.42% and the indirect effect of work environment variables through its relationship with leadership style variables of 0.0274 or 2.74%. The direct and indirect influence of 0.2916 or 29.16%; 4) The effect of leadership style variables on work stress variables is 0.0196 or 1.96% and the indirect effect of leadership style variables through its relationship with work environment variables is 0.0274 or 2.74%. So the direct and indirect influence of 0.0470 or 4.7%.